Antrodia camphorata-Derived Antrodin C Inhibits Liver Fibrosis by Blocking TGF-Beta and PDGF Signaling Pathways - Xu, Xin-Yi; Geng, Yan; Xu, Hao-Xiang; Ren, Yilin; Liu, Deng-Yang; Mao, Yong (Frontiers in Molecular Biosciences, 2022)
Hepatic stellate cells (HSCs) play an essential role in the development of liver fibrosis. Antrodia camphorata (A. camphorata) is a medicinal fungus with hepatoprotective effect. This study investigated whether Antrodin C, an A. camphorata-fermented metabolite, could exert a protective role on liver fibrosis both in vitro and in vivo. The anti-fibrotic effect of Antrodin C was investigated in CFSC-8B cell (hepatic stellate cell line) stimulated by transforming growth factor-β1 (TGF-β1) or platelet-derived growth factor-BB (PDGF-BB) in vitro and in CCl4 induced liver fibrosis in mice. Antrodin C (50 μM) inhibited TGF-β1 or PDGF-BB stimulated CFSC-8B cell activation, migration and extracellular matrix (ECM) accumulation (all p<0.05). Antrodin C (3, 6mg/kg/d) oral administration reduced the degree of liver fibrosis induced by CCl4 in mice. Antrodin C down-regulated the expression of α-smooth muscle actin (α-SMA) and Collagen I in fibrotic livers. Furthermore, Antrodin C ameliorated alanine aminotransferase (ALT) and aspartate aminotransferase (AST) elevation in serum (all p<0.05). Mechanistically, Antrodin C executes its anti-fibrotic activity through negatively modulate TGF-β1 downstream SMAD Family Member 2 (Smad2), AKT Serine/Threonine Kinase 1 (AKT), extracellular signal-regulated kinase (ERK), and P38 MAP Kinase (P38), as well as PDGF-BB downstream AKT and ERK signaling pathways. Antrodin C ameliorates the activation, migration, ECM production in HSCs and CCl4-induced liver fibrosis in mice, suggesting that Antrodin C could serve as a protective molecule against liver fibrosis.